A Cyber‐Physical System Simulator for Risk‐Free Transport Studies. (12th February 2014) - Prendinger, Helmut; Miska, Marc; Gajananan, Kugamoorthy; Nantes, Alfredo
Abstract The article introduces a novel platform for conducting controlled and risk‐free driving and traveling behavior studies, called Cyber‐Physical System Simulator (CPSS). The key features of CPSS are: (1) simulation of multiuser immersive driving in a three‐dimensional (3D) virtual environment; (2) integration of traffic and communication simulators with human driving based on dedicated middleware; and (3) accessibility of multiuser driving simulator on popular software and hardware platforms. This combination of features allows us to easily collect large‐scale data on interesting phenomena regarding the interaction between multiple user drivers, which is not possible with current single‐user driving simulators. The core original contribution of this article is threefold: (1) we introduce a multiuser driving simulator based on DiVE, our original massively multiuser networked 3D virtual environment; (2) we introduce OpenV2X, a middleware for simulating vehicle‐to‐vehicle and vehicle‐to‐infrastructure communication; and (3) we present two experiments based on our CPSS platform. The first experiment investigates the "rubbernecking" phenomenon, where a platoon of four user drivers experiences an accident in the oncoming direction of traffic. Second, we report on a pilot study about the effectiveness of a Cooperative Intelligent Transport Systems advisory system.